Tritium Breeding Performance Analysis of HCLL Blanket Fusion Reactor Employing Vanadium Alloy (V-5Cr-5Ti) as First Wall Material - Indah Rosidah Maemunah; Zaki Su’ud; Abdul Waris; Dwi Irwanto (Science and Technology of Nuclear Installations)
Neutronic analysis in the HCLL blanket module has been established, and the calculation was performed by the ITER team, including the first wall (FW). In this study, seven materials have been investigated for FW material by considering characteristics such as high neutron fluence capability, low degradation, under irradiation, and high compatibility for blanket material. A three-dimensional configuration simulated in MCNP5 program codes was performed to investigate the neutronic performance and radiation damage effect. Employing seven candidates are vanadium carbide (VC), titanium carbide (TiC), vanadium alloy (V-5Cr-5Ti), graphite (C), tungsten alloy (W-CuCrZr), ceramic alloy (SiC), and HT-9 to study optimization of FW materials configurated in the HCLL blanket module. This novelty study concludes that vanadium alloy (V-5Cr-5Ti) is becoming a promising material candidate. This alloy has the highest number of neutronic performing for 1.27 TBR and 1.26 in multiplication energy factor in all investigations. Meanwhile, the amount of atomic displacement, hydrogen, and helium production are around 22.31 appm, 765.55 appm, and 281.57 appm, respectively. Even though vanadium alloy has a reasonably high radiation damage effect, it is still tolerable compared to several thresholds of DPA. So, it is considered excellent material for FW. Nevertheless, this alloy can replace after 13.45 years for radiation damage.